Pathogenesis of Chronic Urticaria: An Overview - Sanjiv Jain (Dermatology Research and Practice)
The pathogenesis of chronic urticaria is not well delineated and the treatment is palliative as it is not tied to the pathomechanism. The centrality of mast cells and their inappropriate activation and degranulation as the key pathophysiological event are well established. The triggering stimuli and the complexity of effector mechanisms remain speculative. Autoimmune origin of chronic urticaria, albeit controversial, is well documented. Numerical and behavioral alterations in basophils accompanied by changes in signaling molecule expression and function as well as aberrant activation of extrinsic pathway of coagulation are other alternative hypotheses. It is also probable that mast cells are involved in the pathogenesis through mechanisms that extend beyond high affinity IgE receptor stimulation. An increasing recognition of chronic urticaria as an immune mediated inflammatory disorder related to altered cytokine-chemokine network consequent to immune dysregulation resulting from disturbed innate immunity is emerging as yet another pathogenic explanation. It is likely that these different pathomechanisms are interlinked rather than independent cascades, acting either synergistically or sequentially to produce clinical expression of chronic urticaria. Insights into the complexities of pathogenesis may provide an impetus to develop safer, efficacious, and targeted immunomodulators and biological treatment for severe, refractory chronic urticaria.